Elastic limit: The role of university-focused venture capital firms in extending knowledge and technology transfer - Padilla-Meléndez, Antonio; Lockett, Nigel; Fuster-Martín, Elena; Jack, Sarah (My University, 2016)
This paper has two main objectives. Firstly, to identify the role of the university-focused intermediaries, specifically UVCs, in order to explain how they interact at the early stage of USO creation, particularly regarding knowledge sharing. Secondly, to analyse whether they change their position once the USO is developed. This gives rise to two Research Questions: How does knowledge sharing occur in the dynamics of a university-based entrepreneurial ecosystem? And Do particular participants, such as UTTOs or UVCs, always occupy the same role and position within the university-based entrepreneurial ecosystem?
Keywords: Relaciones universidad-empresa; Academic entrepreneurship; Spin outs; University venture capital